Intracranial foreign body in a globe-perforating injury - Tuerkcueoglu, Peykan; Aydogan, Semih (Canadian Ophthal Soc, 2006)
Case report: To report a case with an intracranial foreign body in the setting of a globe-perforating injury. A 53-year-old man experienced a sudden pain in his right eye while he was breaking a stone with a sledgehammer. Upon examination, a 1.5 mm superomedial corneoscleral perforation site was noted. Cranial sections of axial orbital computed tomography (CT) revealed a foreign body at the middle cranial fossa. Comments: A high index of suspicion is required to detect an intracranial foreign body in ocular injuries. Orbital CT must be included in preoperative evaluation of these patients and cranial sections must also be examined carefully.
Keywords: globe perforation; intracranial foreign body; imaging